Context, acute tolerance, and subjective response affect alcohol-impaired driving decisions - Motschman, Courtney A.; Warner, Olivia M.; Wycoff, Andrea M.; Davis-Stober, Clintin P.; McCarthy, Denis M. (Psychopharmacology, 2020)
Rationale Alcohol intoxication produces effects that can impair judgment and increase engagement in risky behaviors, including alcohol-impaired driving (AID). Real-world AID decisions are informed by contextual circumstances and judgments of associated risk. How individuals vary in their AID decision-making across contexts and whether subjective alcohol responses (stimulation, sedation, acute tolerance) differentially affect AID decisions are critical, but under-studied research questions. Objectives We systematically investigated predictors of AID decisions at different hypothetical driving distances across the blood alcohol concentration (BAC) curve. Methods Young adults ( n = 40; 55% female) completed two laboratory sessions in a within-subjects alcohol/placebo design. At multiple points along the BAC curve ( M peak BAC = 0.101 g%), participants rated their subjective intoxication, stimulation, sedation, and perceived dangerousness of driving prior to indicating their willingness to drive distances of 1, 3, and 10 miles. Multilevel mixed models assessed within- and between-person predictors of the maximum distance participants were willing to drive at matched BACs on the ascending and descending limb. Results Under intoxication (but not placebo), participants were willing to drive greater distances on the descending versus ascending limb. At the momentary level, participants were willing to drive further when they felt less intoxicated, stimulated, and sedated, and perceived driving as less dangerous. Conclusions Individuals differed in the distance they were willing to drive as a function of indicators of intoxication, implicating driving distance as an important contextual factor relevant to AID decisions. Individuals may simultaneously perceive themselves as “unsafe” to drive, but “safe enough” to drive short distances, particularly when BAC is falling.